The Influence of Transformational and Transactional Leadership on Organisational Performance: A Case of a Higher Education Institution in Tanzania - Kelvin Mwita; Gloria Mrema (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aimed at examining the influence of transformational and transactional leadership on organisational performance by using Ruaha Catholic University of Tanzania as a case study. Quantitative data was collected from 130 employees of the university by using a standard questionnaire. Data analysis was done by using descriptive and inferential statistics, specifically linear regression. Descriptive results were presented using frequencies, means and standard deviations while results from inferential statistics were presented in the form of correlations and regressions.  Transformational and transactional leadership were found to have mean values that are above average score and the difference between the two leadership styles were not significantly big. However, the findings show that leaders practised more of transactional leadership than transformational leadership since transactional leadership had higher mean score value. Moreover, the study found that both transformational and transactional leadership have significant positive linear relationships with organisational performance. The findings give an implication that both transformational and transactional leadership can be used concurrently to bring about positive results in an organisation.